Gambaran Tingkat Pengetahuan Kader Posyandu Tentang Penularan Hiv/Aids Dari Ibu Ke Anak Di Desa Cileles - Fardila Elba; Wiajaya Wiajaya; Farah Dina Nurfathia (Sehat MasadaJurnal, 2018)
In Indonesia, in 2014 the total number of pregnant women was 5,192,427, only 5,167 (0.1%) were tested for HIV. The HIV virus can be transmitted from HIV-infected mothers to their children during pregnancy, during labor and breastfeeding. HIV transmission from mother to child can actually be intervened with PMTCT. However, the coverage is still low at 8% in 2010. Basic level health services can be assisted by cadres in MCH services by motivating and supporting pregnant women by motivating pregnant women to test HIV / AIDS. This study used a cross-sectional approach. The sample in this study was a Posyandu Cadre in Cileles Village. Sampling using total sampling technique with the number of samples that correspond to the inclusion and exclusion criteria as many as 53 respondents. The research shows that the level of good knowledge is mostly in the age group of 20-35, the best knowledge is mostly at the junior high school level, and the best knowledge is mostly on cadres with a working period of 0-5 years. Most respondents have sufficient knowledge about HIV / AIDS transmission from mother to child. Sufficient knowledge can be obtained from various sources, such as: mass media, books, and information obtained from health workers.